Who's on Fire? Household Characteristics and the Formation of Inflation Expectations - Lovisa Reiche; Gabriele Galati; Richhild Moessner; Maarten van Rooij (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We study how consumers form and revise inflation expectations using a unique, highly balanced monthly panel of Dutch households. We develop a Bayesian framework that nests Full-Information Rational Expectations (FIRE) alongside common forecasting heuristics and test it by recovering person-specific belief-updating rules from individual time-series regressions. Our novel individual-level design reveals substantial heterogeneity in how households process information over time. On average, consumers systematically overreact to current inflation, echoing patterns found for professional forecasters. Only 2.5 percent, predominantly wealthier, more educated men, behave consistently with FIRE. Most consumers rely on simple heuristics, especially adaptive expectations. Our results show that heuristic learning, not FIRE, characterizes expectation formation for the vast majority of households. Crucially, heterogeneity in belief updating is both large and systematic.
Keywords: E31; E37; E70; 330; household inflation expectations; FIRE; heuristic learning